A Improving Student Achievement Through Teacher Characteristics: Literature Review and Educational Policy Recommendations to Improve Teaching Quality - Liputo, Muhammad Arif (Jurnal Pendidikan Ekonomi, 2026)
ABSTRACT This article examines the influence of teacher characteristics on student achievement, focusing on key factors such as formal education, teaching experience, and teacher self-efficacy. Based on a literature review, this study found that teacher characteristics play a significant role in improving teaching quality and student academic achievement. Furthermore, student perceptions of teaching quality also play a significant role as a mediator in strengthening the influence of teacher characteristics on student achievement. This study also identified that educational policies that support ongoing teacher training, transparent performance evaluations, and rewards for outstanding teachers are essential to improving teaching quality in Indonesia. Developing policies that support the development of teacher characteristics is expected to create a more effective learning environment, leading to improved student achievement throughout Indonesia. This article also provides suggestions for further research on other factors influencing the relationship between teacher characteristics and student achievement, as well as the influence of social and cultural contexts on education policy in Indonesia. KEYWORDS teacher characteristics, student achievement, education policy, self-efficacy, teacher training.